Comparative study of acid and basic catalysis in microwave assistance of Willgerodt-Kindler reaction for thiobenzamides and derivatives synthesis. - AGNIMONHAN, Finagnon H.; AHOUSSI, AKANNI LÉON; KPOVIESSI DOSSOU, SIKA SALOME; GBAGUIDI, Ahokannou Fernand; KAPANDA, N. Coco; MOUDACHIROU, MANSOUROU; Poupaert, Jacques; Accrombessi, C. Georges (My University, 2014)
Montmorillonite K-10 was used in the acid catalysis of the Willgerodt-Kindler’s reaction (WK) under microwave heating for synthesis of thiobenzamides. Yields of 67% and 43% for the synthesis of morpholin-4- yl (phenyl) methanethione (1) and [4 - (dimethylamino) phenyl] (morpholin-4-yl) methanethione (2) respectively, showed that the mixture (aldehyde, sulfur, morpholine and K-10) is quite suitable for this reaction. This enables to deduct that the conditions of acid catalysis with the K-10 are favourable to the WK’s reaction of carbonyl compounds. Furthermore, yields of 81% and 74% respectively for the synthesis of thioamides 1 and 2 in basic catalysis with 4-methylmorpholine allows to confirm that this reaction is more advantageous in basic catalysis. The structures of thioamides synthesized were characterized and confirmed by spectroscopy Infrared (IR), nuclear magnetic resonance (1H and 13C NMR) and mass spectrometry (MS).
Keywords: Montmorillonite K-10; 4-methylmorpholine; morpholin-4-yl(phenyl)methanethione; [4-; (dimethylamino)phenyl](morpholin-4-yl)methanethione.